Identifying Catalytic Active Sites of Trimolybdenum Phosphide (Mo3P) for Electrochemical Hydrogen Evolution. Issue 22 (2nd May 2019) - Kondori, Alireza; Esmaeilirad, Mohammadreza; Baskin, Artem; Song, Boao; Wei, Jialiang; Chen, Wei; Segre, Carlo U.; Shahbazian‐Yassar, Reza; Prendergast, David; Asadi, Mohammad
Abstract: Solid‐state electrocatalysis plays a crucial role in the development of renewable energy to reshape current and future energy needs. However, finding an inexpensive and highly active catalyst to replace precious metals remains a big challenge for this technology. Here, tri‐molybdenum phosphide (Mo3 P) is found as a promising nonprecious metal and earth‐abundant candidate with outstanding catalytic properties that can be used for electrocatalytic processes. The catalytic performance of Mo3 P nanoparticles is tested in the hydrogen evolution reaction (HER). The results indicate an onset potential of as low as 21 mV, H2 formation rate, and exchange current density of 214.7 µmol s −1 g −1 cat (at only 100 mV overpotential) and 279.07 µA cm −2, respectively, which are among the closest values yet observed to platinum. Combined atomic‐scale characterizations and computational studies confirm that high density of molybdenum (Mo) active sites at the surface with superior intrinsic electronic properties are mainly responsible for the remarkable HER performance. The density functional theory calculation results also confirm that the exceptional performance of Mo3 P is due to neutral Gibbs free energy (Δ G H* ) of the hydrogen (H) adsorption at above 1/2 monolayer (ML) coverage of the (110) surface, exceeding the performance of existing non‐noble metal catalysts for HER. Abstract : Solid‐state electrocatalysis plays a crucial role to reshape present and future energy needs . Here, trimolybdenum phosphide is discovered as a novel inexpensive material with superior catalytic properties. Electrochemical experiments, atomic scale characterizations, and computational studies indicate that the unique structure of this catalyst provides a high density of active sites at the surface with outstanding intrinsic electronic properties pivotal to electrocatalytic reactions.